Manajemen Program Bahasa Arab di Pondok Pesantren Daarul Ukhuwwah Putri 2 Malang - Dian Ahmad Jufrih; Abdul Wahab Rosyidi; Usfiyatur Rusul (Mu'allim, 2023)
The purpose of this research is to describe matters related to the managemen of the Arabic Language Program at the Daarul Ukhuwwah Putri 2 Islamic Boarding School in Malang. From the aspect of planning, organizing, implementing and evaluating. In this study, researchers used descriptive qualitative methods. Where the data obtained by the researcher comes from observation and interview data, which is then carried out by analyzing data condensation, data display and Drawing and Verifying Conclusions. The results showed that the managemen of Arabic language learning program planning at Daarul Ukhuwwah adopted the Kuliiyatul Muallimin Al Islamiyah Curriculum at Pondok Modern Darussalam Gontor, Ponorogo. At the organizing stage, an organizational structure is formed for each division. One of them is the Central Language section which is held directly by the ustadzah. The implementation stages of the Arabic language program include: Arabic language learning in class, distribution of mufrodat, muhadasah activities, muhadhoroh activities and language festivals. At the evaluation stage, Pondok Pesantren Daarul Ukhuwwah Putri 2 Malang consists of daily, weekly, monthly, and annual evaluations.